A Contrastive Study 0f British and American English Pronunciation for Students - Eny Rein Sihombing; Adelia Sidabutar; Immanuel Simbolon; Bloner Sinurat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
English is a language used all around the world, and it has many different ways of being spoken depending on where people are from. The two main ways are British English and American English. These two versions are especially important in schools, media, and international communication. This paper examines the pronunciation differences between British and American English, and how these differences may impact students’ language learning. Rather than conducting experiments, this paper draws upon theories and descriptions from established studies in phonetics and linguistics. The paper focuses on differences in vowels and consonants, how words are stressed, how sentences go up and down in pitch, and processes like rhoticity and flapping. It also gives examples of how these differences show up in classrooms, especially for Indonesian learners who are often exposed to both versions through books, online content, and language learning tools. In the end, the paper suggests that learning pronunciation should focus on making speech clear and understandable, rather than sticking strictly to one way of speaking.